The participation of ict in activities of economic subjects in small economy - Valentina Mucunska Palevska; Blagica Novkovska (UTMS Journal of Economics, 2018)
The use of digital technology in business is of particular interest to researchers because information and communication tools generate changes that reflect on the productivity of organizations and the economic development of countries. This paper examines the relationship between information and communication technologies (ICT) and economic entities in small countries, i.e. the level of investment and application of digital technology in the operation of economic entities in the Republic of Macedonia and the impact on economic growth and development. Relevant data for the period from 2013 to 2017 were used to analyze the situation. Based on the obtained indicators, it has been shown that economic entities are insufficiently investing in information and communication technology that results in low level of application in the operation, and thus reduced productivity and profitability. It is concluded that attracting foreign direct investments and increasing exports require Macedonian organizations to change their existing way of working by increasing the use of ICTs and actively engaging in the implementation of E-Business in their operations.
Keywords: D83; L86; L96; 330; investing in ICT; digital economy; productivity